Theory of Mind and Concealing vs. Forthcoming Communication in Adolescence - Lavoie, Jennifer; Talwar, Victoria (Frontiers in Psychology, 2022)
Concealing information requires that adolescents manage the information that they share, which requires cognitive skills, for example theory of mind (ToM). This study explored motivations for concealment that early adolescents (N = 90, M = 12.81 years, SD = 5.10 months, range 12-14 years, 58% female) endorsed concealing or disclosing to friends and parents, in relation to their theory of mind. We found that adolescents broadly endorsed disclosure to both parents and friends, even when it might mean they would face consequences, be impolite (by not protecting another’s feelings), or face negative identity-related emotions. We found that ToM ability was associated with a tendency to endorse being forthcoming and sharing information with both friends and parents. These findings provide new insight into how the relation between ToM and concealment may change with age, specifically how in early adolescence it may foster open communication rather than concealment as is the case in early and middle childhood.